Mitigating Workplace Accident Risks through Training on the Introduction and Simulation of Personal Protective Equipment Use among Construction Workers: Mitigasi Risiko Kecelakaan Kerja melalui Pelatihan Pengenalan dan Simulasi Penggunaan Alat Pelindung Diri pada Pekerja Konstruksi - Soehardi, Fitridawati; Rahmat, Hendri; Idris, Marlaily; Dinata, Marta; Elizar, Elizar; Dewi, Sri Hartati; Ardiansyah, Rony; Sari, Yusra Aulia; Panjaitan, Yohana Pinta Uli; Rahmadhany, Rezky Aulia (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The construction industry has a high rate of workplace accidents due to the low compliance of workers in using Personal Protective Equipment (PPE). To address this issue, a community service program was conducted in the form of training on the introduction and simulation of PPE usage aimed at improving the knowledge, skills, and awareness of construction workers. The program was implemented using an educational–participatory approach through four stages: needs analysis, occupational safety counseling, simulation-based field practice training, and evaluation with monitoring. The evaluation results showed an increase in participants’ knowledge by 36,48%, from an average pre-test score of 56.33% to 95,81%, and an improvement in compliance with PPE usage by 36.42%. Moreover, 92,22% of participants reported becoming more disciplined in using PPE after the training. This program demonstrates that simulation-based methods effectively foster safe work behavior. It is recommended that similar training be conducted regularly, supported by internal supervision and reminder posters to strengthen a sustainable safety culture.